Influence Electronic Word Of Mouth, Price, And Product Quality On Decisions Purchase At Cafe Mr. Takoyaki In Denpasar - Ni Putu Eka Santiari; I.B Udayana Putra; Ni Made Rustini (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
This research aims to explore the influence of Electronic Word of Mouth (EWOM), price and product quality on consumer purchasing decisions at Cafe Mr. Takoyaki in Denpasar. This research uses quantitative methods with a sample size of 100 respondents selected using the Slovin formula based on the consumer population of Cafe Mr. Takoyaki totaling 10,528 people. All data obtained from the questionnaire distribution is suitable for use, then analyzed using the classic assumption test, multiple linear regression, hypothesis testing (f test and t test). The results of the analysis show that (1) Electronic Word of Mouth, price and product quality significantly influence purchasing decisions at Cafe Mr. Takoyaki. (2) Electronic Word of Mouth has a positive and significant effect on purchasing decisions at Cafe Mr. Takoyaki in Denpasar. (3) Price has a positive and significant effect on purchasing decisions at Cafe Mr. Takoyaki in Denpasar. (4) Product quality has a positive and significant effect on purchasing decisions at Cafe Mr. Takoyaki in Denpasar. Therefore, based on this research it can be concluded that Electronic Word of Mouth, price and product quality have a significant role in influencing purchasing decisions at Cafe Mr. Takoyaki in Denpasar.